Thickness-dependent Electrical and Piezoelectric Properties of Lead-Free Ferroelectric Ba0.8Sr0.2TiO3 Thin Films - D.A. Kiselev; S.A. Levashov; M.S. Afanasiev; A.M. Kiselev; G.V. Chucheva (Журнал нано- та електронної фізики)
The thickness dependent of electrical and piezoelectric properties of lead-free ferroelectric Ba0.8Sr0.2TiO3 thin films is reported. Ba0.8Sr0.2TiO3 (BST 80/20) thin films for various thickness, ranging from 150 nm to 550 nm, were prepared by high-frequency reactive sputtering of a ceramic target in an oxygen atmosphere on p-type Si substrate. Memory windows and effective dielectric constant of the BST film in Au/BST/Si thin film capacitors is found to increase with the increasing thickness of the film. Domain structure, domain switching and hysteresis loops of the BST 80/20 thin film were investigate via the piezoresponse force microscopy. Complete domain switching and strong piezoresponse are found in the ferroelectric BST film. The piezoelectric coefficient () and the remnant piezoelectric response (ΔPR) of BST 80/20 films is found to increase with the thickness of the film.